Vernacular Books and Religious Dissent in Early Modern Italy: A Study of the Ahmanson-Murphy Aldine Collection at UCLA - Vatteroni, Selene Maria (Renaissance and Reformation / Renaissance et Réforme, 2021)
The sixteenth century was a period of tumultuous religious change in Europe as a whole. Italian Cinquecento culture was profoundly shaped by currents for reform and counter-reform; printed vernacular literature soon came to represent an excellent vehicle for spreading philo-Protestant religious propaganda, but it became a powerful weapon of the Roman counterpart as well. In this article, I will outline a survey of textual materials preserved in the Ahmanson-Murphy Aldine Collection at UCLA, focusing on Italian vernacular works printed between the 1540s and the 1580s. I will consider three aspects of the history of Italian print as related to the Cinquecento religious turmoil: the use of Nicodemite strategies and their effectiveness; the role of Petrarchist poetry as a privileged conduit for evangelizing dissenting doctrinal content; and the development of (para)textual apparatuses intended for instruction and guidance to the reader.